Trisomy 21 dysregulates T cell lineages toward an autoimmunity-prone state associated with interferon hyperactivity - Araya, Paula (2019)
Trisomy 21 (T21) causes Down syndrome (DS), a condition characterized by high prevalence of autoimmune disorders. However, the molecular and cellular mechanisms driving this phenotype remain unclear. Building upon our previous finding that T cells from people with DS show increased expression of interferon (IFN)stimulated genes, we have completed a comprehensive characterization of the peripheral T cell compartment in adults with DS with and without autoimmune conditions. CD8+ T cells from adults with DS are depleted of naïve subsets and enriched for differentiated subsets, express higher levels of markers of activation and senescence (e.g., IFN-γ, Granzyme B, PD-1, KLRG1), and overproduce cytokines tied to autoimmunity (e.g., TNF-α). Conventional CD4+ T cells display increased differentiation, polarization toward the Th1 and Th1/17 states, and overproduction of the autoimmunity-related cytokines IL-17A and IL-22. Plasma cytokine analysis confirms elevation of multiple autoimmunity-related cytokines (e.g., TNF-α, IL17A–D, IL-22) in people with DS, independent of diagnosis of autoimmunity. Although Tregs are more abundant in DS, functional assays show that CD8+ and CD4+ effector T cells with T21 are resistant to Treg-mediated suppression, regardless of Treg karyotype. Transcriptome analysis of white blood cells and T cells reveals strong signatures of T cell differentiation and activation that correlate positively with IFN hyperactivity. Finally, mass cytometry analysis of 8 IFN-inducible phosphoepitopes demonstrates that T cell subsets with T21 show elevated levels of basal IFN signaling and hypersensitivity to IFN-α stimulation. Therefore, these results point to T cell dysregulation associated with IFN hyperactivity as a contributor to autoimmunity in DS.